Potensi Limbah Padat Kelapa Sawit sebagai Antibrowning dan Repellent Aedes Aegypti - La Ode Sumarlin; . Faturrahman; Sri Yadial Chalid (Institut Pertanian Bogor, 2019)
A research was conducted to study the potential of solid oil palm waste as an antibrowning and as a repellent of Aedes aegypt. The amount of oil palm waste is increasing along with the expansion of oil palm plantation. A prevention method is needed to overcome solid, liquid, and gaseous wastes of oil palm which pollute the environment. Cellulose, hemicellulose, and lignin contained in solid waste of oil palm can be anaerobically fermented naturally to produce garbage enzyme which can be used as an antibrowning and as a repellent of Aedes aegypt. Browning index and polyphenol level were tested with UV Vis spectrophotometry while repellent level was tested using Aedes aegypti mosquito and a formula applied to the skin. The result showed that the acidity level (pH) was between 3.54-3.15. The highest antibrowning properties were found in oil palm fiber (SKS) and palm oil cake (BKS) with a browning index value of 0.037 with a relative inhibition (antibrowning) of 78%. Meanwhile, the highest repellent properties toward Aedes aegypti was showed by the on palm empty fruit bunch (TKS) + oil palm fiber (SKS) with 79.76% effective rejection percentage. There fore, fermented oil palm waste has an antibrowning effect and a repellent Aedes aegypti mosquito.